DFT modelling studies of spectroscopic properties and Medium Effects on Molecular Reactivity of Secnidazole in different solvents - Hssaın, Ala (Niyazi BULUT, 2022)
The spectroscopic and optoelectronic investigations of (hydroxyl-2-propyl)-1-methyl-2-nitro-5-imidazole (secnidazole, C_7 H_11 N_3 O_3) molecule were performed using C13 and H1 NMR chemical shifts, FT-IR spectroscopies. Molecular geometric optimizations, HOMO-LUMO properties and molecular electrostatic potential (MPE) were studied using B3LYP functional in DFT method at the cc-pVDZ basis set. UV-Vis spectra of the titled molecule in several solvents (water, dimethyl sulfoxide (DMSO), nitromethane, acetone, and tetrahydrofuran (THF) were investigated theoretically with the aforementioned model method. The solvents have an effective role in the optoelectronic properties of the secnidazole molecule. From non-polar to polar solvents, the (HOMO and LUMO) bandgap energy of secnidazole was found to be decreased except THF solvent. Furthermore, the research aims at investigating the medium effects on solvation free energy, polarizability, dipole moment, first-order hyper-polarizability as well as several molecular properties such as chemical potential, electronegativity, chemical hardness and softness, electrophilicity index of secnidazole (SNZ). The aforementioned method and basis set was used for all kinds of computations in the gas phase and solution. The Solvation Model on Density (SMD) was applied to the aforementioned solvent systems to calculate the solvent polarity effect on dipole moment, free energy, and molecular properties of the (SNZ) molecule. The free energies have gradually increased with a decrease in the solvent dielectric constant i.e. as solvent polarity decreases, the solvation energy increases. From polar to non-polar solvents, the dipole moment of secnidazole was found to be decreased. In various solvents, the dipole moment of secnidazole was greater than that of the gas phase. With the decrease of the solvent dielectric constant, the first-order hyperpolarizability and polarizability have also been decreased. Besides, electronegativity, the chemical potential, and electrophilicity index were decreased continuously from polar to non-polar solvent, except in THF. Secnidazole’s electronegativity, chemical potential, and electrophilicity index were higher in THF than in acetone. However, with increasing solvent polarity, chemical hardness decreased and the inverse relationship was noticed in the case of chemical softness. The obtaining results in this computational investigation may lead to a better understanding of the stability and reactivity of secnidazole and will be helpful for the use of the title compound as reaction intermediates and pharmaceuticals.
Keywords: Metrology; Applied and Industrial Physics; Metroloji; Uygulamalı ve Endüstriyel Fizik